Ethnobotany, phytochemistry and pharmacological activities of Celtis australis: A review - Khadija Benamar; Saad Ibnsouda Koraichi; Kawtar Fikri-Benbrahim (Shahrekord University of Medical Sciences, 2023)
Celtis australis is a deciduous plant used worldwide in folk medicine to treat various ailments, such as stomach disorders, cough, pimples, joint pain, amenorrhoea, rheumatism, menstrual disorders, and herpes. The present review aims to document and summarize different works regarding the ethnomedicinal uses, phytochemistry, and biological activities of different parts (fruits, barks, leaves, and seeds) of this medicinal plant. For data collection, Google scholar, Science direct, Scopus, PubChem, and PubMed databases were used. This study shows that C. australis contains several bioactive compounds, exhibiting various pharmacological activities mainly hepatoprotective, analgesic, anti-inflammatory, cytotoxic, antioxidant, and antimicrobial properties. Thus, C. australis is a promising plant that can be exploited in the treatment of various diseases.